Insights into the HIV Latency and the Role of Cytokines - Joseph Hokello; Adhikarimayum Lakhikumar Sharma; Manjari Dimri; Mudit Tyagi (Pathogens, 2019)
Human immunodeficiency virus-1 (HIV-1) has the ability to infect latently at the level of individual CD4+ cells. Latent HIV-1 proviruses are transcriptionally silent and immunologically inert, but are still capable of reactivating productive lytic infection following cellular activation. These latent viruses are the main obstacle in the eradication of HIV-1, because current HIV-1 treatment regimens are ineffective against them. Normal immunological response against an antigen activates CD4+ naïve T cells. The activated CD4+ naïve T cells undergo cell cycle, resulting in further transformation and profound proliferation to form effector CD4+ T-cells. Notably, in HIV-1 infected individuals, some of the effector CD4+ T cells get infected with HIV-1. Upon fulfillment of their effector functions, almost all activated CD4+ T cells are committed to apoptosis or programmed cell death, but a miniscule fraction revert to quiescence and become resting memory CD4+ T cells to mediate a rapid immunological response against the same antigen in the future. However, due to the quiescent nature of the resting memory T cells, the integrated HIV-1 becomes transcriptionally silent and acquires a latent phenotype. Following re-exposure to the same antigen, memory cells and integrated HIV-1 are stimulated. The reactivated latent HIV provirus subsequently proceeds through its life cycle and eventually leads to the production of new viral progeny. Recently, many strategies against HIV-1 latency have been developed and some of them have even matured to the clinical level, but none can yet effectively eliminate the latent HIV reservoir, which remains a barrier to HIV-1 cure. Therefore, alternative strategies to eradicate latent HIV need to be considered. This review provides vital knowledge on HIV latency and on strategies to supplement highly active anti-retroviral therapy (HAART) with cytokine-mediated therapeutics for dislodging the latent HIV reservoirs in order to open up new avenues for curing HIV.